DOI: 10.1007/978-1-4020-9557-3_29
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Electrospinning of Nanofibers

Abstract: A fast discrete model for the simulations of thin charged jets produced during the electrospinning process is derived, based on an efficient implementation of the boundary element method for the computation of electrostatic interactions of the jet with itself and with the electrodes. Short-range electrostatic forces are evaluated with slender-body analytical approximations, whereas a hierarchical force evaluation algorithm is used for long-range interactions. Qualitative comparisons with experiments is discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…This search of the most stable process has been performed following the guideline of previous works conducted with some other polymer trials. [55,56] The selected parameters have been maintained for the spinning of the three materials: PLLA0, PLLA1, and PLLA5. There are some key parameters that could affect the process in a greater extent than others.…”
Section: Electrospinning Process Setupmentioning
confidence: 99%
“…This search of the most stable process has been performed following the guideline of previous works conducted with some other polymer trials. [55,56] The selected parameters have been maintained for the spinning of the three materials: PLLA0, PLLA1, and PLLA5. There are some key parameters that could affect the process in a greater extent than others.…”
Section: Electrospinning Process Setupmentioning
confidence: 99%
“…For example, Kowalewski et al [32] demonstrated for the case of glycerol a stabilization purely by the viscous forces of the Newtonian liquid. However, this viscosity-controlled stabilization is possible only to stretch ratios ε on the order of O (10).…”
Section: Shear Rheologymentioning
confidence: 99%
“…An efficient handling of long-range interactions can theoretically achieve O (n log n) operation count, or even O (n) for the fast multipole method (FMM). The proposed here treecode algorithm [7] considers particle-cluster interactions and achieves O (n log n) complexity. Generally it is a time-dependent three-dimensional generalization of known slender models [2,4,5,8], and solves the mass and momentum conservation equation for the Maxwell viscoelastic fluid.…”
Section: Copyright Line Will Be Provided By the Publishermentioning
confidence: 99%
“…A small random perturbation to the position of each element introduced at the inlet is imposed, so as to initiate the bending instability. The magnitude of this perturbation has no notable influence on the simulation results, provided that it is small enough [7].…”
Section: Copyright Line Will Be Provided By the Publishermentioning
confidence: 99%